Toxic Jealousy and the Collapse of Rationality in Shakespeare’s Othello: A Psychological Literary Criticism Study - Fiza Rauzika Altasa Altasa; Evi Zulida; Rahmiati Rahmiati; Muhammad Arif Sanjaya; Irma Dewi Isda (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study analyzes toxic jealousy and its destructive impact on the collapse of rationality in William Shakespeare’s Othello. The objective of this study is to explain how jealousy gradually destroys Othello’s emotional stability, trust, and rational judgment throughout the play. This study employed a descriptive qualitative method using a psychological approach to literary criticism to examine psychological dimensions represented through literary characters and emotional experiences. The data were collected from dialogues, actions, and character expressions in the play, particularly those related to Othello’s emotional transformation. The findings revealed that Othello’s toxic jealousy did not emerge suddenly but developed through interconnected psychological factors involving emotional vulnerability, psychological instability, and external manipulation. These factors gradually intensified Othello’s insecurity and suspicion toward Desdemona, resulting in obsessive suspicion, distorted judgment, and the collapse of rationality. Consequently, Othello experienced psychological deterioration that ultimately led him toward tragic action and self-destruction. This study concludes that Shakespeare portrays jealousy as a destructive psychological force capable of influencing perception, behavior, and moral judgment. Furthermore, this study contributes to psychological literary studies by emphasizing toxic jealousy as a central factor influencing Othello’s psychological transformation and tragic downfall.